Exploring the Trade-Off between Language Simplicity and Execution Efficiency: A Study Using Crython and LLVM - Soham Malakar,; Sreekanya Pal,; Nazlee Rahman,; Asoke Nath, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Contemporary programming languages often pose a challenge due to either complex syntax or performance limitations, especially in dynamically typed environments. The language proposed in this paper, Crython, aims to mitigate these challenges by offering a beginner-friendly, Python-like syntax combined with performance that approaches that of C. It is built with a custom lexer, employs a Pratt parser for expression handling, and uses a Recursive Descent parser for statements. Code generation is powered by LLVM, leveraging its robust toolchain to simplify backend implementation and deliver high execution speed. While the syntax is intentionally similar to Python to facilitate ease of adoption, it also addresses certain ambiguities and inconsistencies found in Python’s design. The paper includes performance benchmarks across multiple languages to demonstrate the efficiency and competitiveness of the proposed language.
Keywords: Programming Language Design; Syntax Simplicity; LLVM Code Generation; Pratt Parser; Performance Benchmarking; Python-like Syntax